ESTADO, POLÍTICAS PÚBLICAS E PERSPECTIVAS DO DESENVOLVIMENTO BRASILEIRO - Liana Maria da Frota Carleial (Universidade Federal do Maranhão, 2012)
This article shows the relationship between State, public policies and development. Which gains extreme relevance in the phase of capitalism dominated by finance, especially after the crisis of 2008, whose expansion and consequences are not totally understood. It points out that the crisis brought back to world scenery intense demonstrations by civil society dissatisfied with the greed of capitalism, but it also questions the capacity of governments to solve social matters which reach populations and, therefore, the form of representative democracy in force. Brasil goes through a special moment of its recent trajectory for it managed to get back its investments, the growth of PIB and of formal employment. In this context, this article questions the possibility which reverts, in fact, our underdevelopment.